HERITAGE JEOPARDIZED: NEED FOR EDUCATION REVALORIZATION IN COTE D’IVOIRE - Kouassi, Eba Eric Anselme (European Scientific Journal, ESJ, 2014)
Young generations are said to be the spearhead of the future. Thus, to ensure the development of Cote d’Ivoire after its independence in 1960, Ivorian authorities implemented a strong education policy that produced highly qualified and skillful workers and leaders. However the recent world economic crisis, doubled with the country’s sociopolitical instability, has resulted in seriously affecting the country’s chances of sustainable growth. To find a solution to the development issue, we assumed that education can play a major role. Consequently, we conducted a study in Ivorian middle and high schools in the aim of designing a new way to involve Ivorian young people in the development process of their country. We then came to the conclusion that the country will difficultly use its youth if a profound reform of its education policy and environment is not rapidly undertaken. Indeed our paper found Ivorian students at the crossroads, undereducated, uncertain and sometimes at ease in their ignorance. It also pointed out the fact that parents and educators did not enough play their role of guidance and assistance. The logical consequence is that Ivorian pupils lack of orientation and conviction.